HEPS-BPIX, a hybrid pixel detector system for the High Energy Photon Source in China. (16th January 2017) - Zhang, J.; Wei, W.; Gu, J.; Shen, W.; Li, Z.; Ning, Z.; Fan, L.; Chen, M.; Lu, Y.; Ma, X.; Jiang, X.; Lan, A.K.; et al.
Abstract: A hybrid pixel detector with single photon counting mode has been designed for the High Energy Photon Source in China. It features a pixel size of 150 μ m × 150 μ m and a frame rate up to 1.2 kHz with 20-bit dynamic range. Six modules were assembled as the first prototype system, covering an area of 9 cm × 10 cm with 360k pixels. Images have been taken using X-ray and synchrotron radiation light, and the preliminary detector performance is presented.